Pemanfaatan Kapasitor Semi Silinder Untuk Pengukuran Kadar Pati Singkong Jenis Thailand - Dina Mauliyani Qoriah; Arif Surtono; Gurum Ahmad Pauzi; Sri Wahyu Suciyati (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
It has been realized that the measurement of the Thai type of cassava starch uses a semi-cylindrical capacitor has been done. This measurement is carried out by providing an input signal to the semi-cylindrical capacitor plate using the IC XR-2206 oscillator with a frequency of 100 kHz. The output signal from the capacitor is in the form of an AC voltage which is then forwarded to the full wave rectifier circuit. The output voltage of the rectifier is a DC voltage, and the results are displayed using a DSO oscilloscope. Cassava starch content was measured by the specific gravity method, and the stress was measured using a semi-cylindrical capacitor. In measuring the starch content, the starch content was 19.12 - 28.76% (range 9.64%) and gave an output voltage of 7.53 - 7.89 V (range 0.36 V). Using the linear regression method, the characteristic equation V = 0.035 KP + 6.871, and the correlation value was equals to 0.985.